Valence band offsets at Cu(In, Ga)Se2/Zn(O, S) interfaces. Issue 9 (19th December 2013) - Adler, Tobias; Botros, Miriam; Witte, Wolfram; Hariskos, Dimitrios; Menner, Richard; Powalla, Michael; Klein, Andreas
<x xml:space="preserve">Abstract</x> The energy band alignment at interfaces between Cu‐chalcopyrites and Zn(O, S) buffer layers, which are important for thin‐film solar cells, are considered. Valence band offsets derived from X‐ray photoelectron spectroscopy for Cu(In, Ga)Se2 absorber layers with CdS and Zn(O, S) compounds are compared to theoretical predictions. It is shown that the valence band offsets at Cu(In, Ga)Se2/Zn(O, S) interfaces approximately follow the theoretical prediction and vary significantly from sample to sample. The integral sulfide content of chemical bath deposited Zn(O, S) is reproducibly found to be 50–70%, fortuitously resulting in a conduction band offset suitable for solar cell applications with Cu(In, Ga)Se2 absorber materials. The observed variation in offset can neither be explained by variation of the Cu content in the Cu(In, Ga)Se2 near the interface nor by local variation of the chemical composition. Fermi level pinning induced by high defect concentrations is a possible origin of the variation of band offset.